2015
DOI: 10.1021/acscatal.5b01554
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Insights into the Hydrogen-Efficient Direct Hydrodeoxygenation Mechanism of Phenol over Ru/TiO2

Abstract: Catalytic reduction of pyrolyzed biomass is required to remove oxygen and produce transportation fuels, but limited knowledge of how hydrodeoxygenation (HDO) catalysts work stymies the rational design of more efficient and stable catalysts, which in turn limits deployment of biofuels. This work reports results from a novel study utilizing both isotopically labeled phenol (which models the most recalcitrant components of biofuels) with D 2 O and DFT calculations to provide insight into the mechanism of the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
208
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(219 citation statements)
references
References 93 publications
9
208
0
2
Order By: Relevance
“…The higher reducibility of Ru/TiO 2 may be explained by the acid–base characteristics of the TiO 2 surface which can catalyze the dissociation of H 2 . Previous computational studies indicated the possibility of a heterolytic cleavage of H 2 at interfacial sites between Ru nanoparticles and basic bridging hydroxyl groups of the TiO 2 surface . For Ru/C, besides the main peak at 150 °C, two additional reduction features at 200 °C and in the 400–600 °C range were observed.…”
Section: Resultsmentioning
confidence: 99%
“…The higher reducibility of Ru/TiO 2 may be explained by the acid–base characteristics of the TiO 2 surface which can catalyze the dissociation of H 2 . Previous computational studies indicated the possibility of a heterolytic cleavage of H 2 at interfacial sites between Ru nanoparticles and basic bridging hydroxyl groups of the TiO 2 surface . For Ru/C, besides the main peak at 150 °C, two additional reduction features at 200 °C and in the 400–600 °C range were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a better mechanistic understanding of which oxygen species participate in desired and undesired oxidation pathways is required to improve selectivity and atom-efficiency. Besides catalytic oxidation reactions, water-mediated proton transfer has other farreaching implications, for instance, in catalytic hydrodeoxygenation of bio-oil [72], electrocatalysis [73][74][75], and any reaction using solid acid catalysts including zeolites [76,77]. Thus, we see numerous opportunities for innovative research on water-assisted catalysis in diverse areas that may ultimately lead to disruptive technologies.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Such interfaces can form the basis of bifunctional catalysis,w here each material contributes its unique functionality to the active site.F or example,b ifunctional catalysts have shown promise for selective hydrodeoxygenation (HDO) of alcohols/aldehydes with aromatic substituents,adesirable path for production of fuels or chemicals from biomass ( Figure 1a). [4][5][6][7][8] Thei mportance of interfacial sites in catalysis suggests that catalyst design should emphasize novel methods for tailoring these interfaces that go beyond using the oxide as as imple catalyst carrier. [4][5][6][7][8] Thei mportance of interfacial sites in catalysis suggests that catalyst design should emphasize novel methods for tailoring these interfaces that go beyond using the oxide as as imple catalyst carrier.…”
mentioning
confidence: 99%